Implementation of Emergency Remote Teaching in Chilean Schools due to COVID-19 - Abarca, Gonzalo Cortes (Journal of Education and e-Learning Research, 2021)
This research emerged from the need to understand educators’ working and teaching conditions during the initial period of distance teaching implementation brought about by the need to continue education in the face of the public health emergency and the suspension of on-site classes in Chilean schools. Thus, the aim of this investigation is to explore Chilean teachers’ perceptions in relation to Emergency Remote Teaching (ERT) within the COVID-19 context. The methodology includes a dynamic online questionnaire to allow a large number of educators to be included in the study. Some of the findings include the substantial curricular adaptation made by teachers, the use of teachers’ own resources to contact students, the overall low level of satisfaction with remote teaching, as well as the increased working hours, and the different connectivity conditions and levels of student participation depending on the socio-economic profile of the school. The conclusions of this research are discussed from the perspective of the hypotheses presented in this study.